Low-wage competition: Pains from trade for medium-wage countries - Lutz Arnold; Michael Heyna (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2020)
The entry of a low-wage country into a world economy with pre-existing wage differentials puts the gains from trade in a former low-wage and then medium-wage country under pressure. If negotiations over the formation of a free trade area cover international transfers, there is a strong presumption that they bring about global free trade and compensation of the mediumwage country if necessary. In the absence of international transfers, by contrast, the medium-wage country is not compensated when global free trade causes a reduction in its gains from trade, and it may even happen that it is not part of the equilibrium free trade area.
Keywords: F11; F61; 330; gains from trade; low-wage competition; North-South trade; freetrade area; core; equality